Dissociable changes in spike and wave discharges following exposure to injected cannabinoids and smoked cannabis in Genetic Absence Epilepsy Rats from Strasbourg. (23rd January 2021) - Roebuck, Andrew J.; Greba, Quentin; Onofrychuk, Timothy J.; McElroy, Dan L.; Sandini, Thaísa M.; Zagzoog, Ayat; Simone, Jonathan; Cain, Stuart M.; Snutch, Terrance P.; Laprairie, Robert B.; Howland, John G.
Abstract: There is significant interest in the use of cannabinoids for the treatment of many epilepsies including absence epilepsy (AE). Genetic Absence Epilepsy Rats from Strasbourg (GAERS) model many aspects of AE including the presence of spike‐and‐wave discharges (SWDs) on electroencephalogram (EEG) and behavioral comorbidities, such as elevated anxiety. However, the effects of cannabis plant‐based phytocannabinoids have not been tested in GAERS. Therefore, we investigated how SWDs in GAERS are altered by the two most common phytocannabinoids, Δ 9 ‐tetrahydrocannabinol (THC) and cannabidiol (CBD), and exposure to smoke from two different chemovars of cannabis. Animals were implanted with bipolar electrodes in the somatosensory cortex and EEGs were recorded for 2 hr. Injected THC (1–10 mg/kg, i.p.) dose‐dependently increased SWDs to over 200% of baseline. In contrast, CBD (30–100 mg/kg, i.p.) produced a ~50% reduction in SWDs. Exposure to smoke from a commercially available chemovar of high‐THC cannabis (Mohawk, Aphria Inc.) increased SWDs whereas a low‐THC/high‐CBD chemovar of cannabis (Treasure Island, Aphria Inc.) did not significantly affect SWDs in GAERS. Pre‐treatment with a CB1R antagonist (SR141716A) did not prevent the high‐THC cannabis smoke from increasing SWDs, suggesting that the THC‐mediated increase may not be CB1R‐dependent. Plasma concentrations of THC and CBD were similar to previously reported values following injection and smoke exposure. Compared to injected CBD, it appears Treasure Island did not increase plasma levels sufficiently to observe an anti‐epileptic effect. Together these experiments provide initial evidence that acute phytocannabinoid administration exerts the biphasic modulation of SWDs and may differentially impact patients with AE. Abstract : Genetic Absence Epilepsy Rats from Strasbourg (GAERS) spontaneously produce spike‐and‐slow wave discharges (SWDs). In the first experiments assessing cannabinoids in GAERS, injected tetrahydrocannabinol (Δ 9 ‐THC) dose‐dependently increased SWDs, whereas injected cannabidiol (CBD) reduced these events. Furthermore, smoke exposure from high‐Δ 9 ‐THC cannabis increased SWDs, but high‐CBD cannabis had no effect. These experiments show dissociable effects using two different exposure paradigms.